Analisis Kinerja Dan Posisi Keuangan Pt Garuda Indonesia Tbk Berdasarkan Indikator Rasio Keuangan, Tingkat Kesehatan Dan Prediksi Keuangan - Triandi Triandi; Ivana Christine (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The purpose of this study was to determine the level of health in the Financial Aspects of the state-owned company PT Garuda Indonesia (Persero) Tbk for the period 2017, 2018 and 2019 using financial ratios based on the Decree of the Minister of SOEs No. KEP-100/KBU/2002 dated June 4, 2002 concerning Assessment of the Health Level of State-Owned Enterprises and analysis of potential bankruptcy using the Altman Z-Score model. The method used in this study is a comparative descriptive quantitative method using a secondary data analysis approach sourced from the consolidated financial statements of PT Garuda Indonesia Tbk. The results showed that the Company's Health Level was measured by the criteria according to the Decree of the Minister of SOEs No. KEP-100/KBU/2002, 2017, 2018 and 2019 respectively, can be classified as Unhealthy in the "BBB" category, because the score is in the range 50 < TS <= 65, and the potential for bankruptcy based on the Altman Z-Score analysis shows PT Garuda Tbk Indonesia during 2017, 2018 and 2019 was in the Distress Zone because it obtained a score of <1.1 or it can be said that the company has a strong potential for bankruptcy. Keywords: Health Level, Bankruptcy Potential, Decree of the Minister of SOEs No. 100/MBU/2002, Altman Z-score.